Giant and reversible room-temperature magnetocaloric effect in Ti-doped Ni-Co-Mn-Sn magnetic shape memory alloys. (1st August 2017) - Qu, Y.H.; Cong, D.Y.; Sun, X.M.; Nie, Z.H.; Gui, W.Y.; Li, R.G.; Ren, Y.; Wang, Y.D.
Abstract: The practical applications of magnetocaloric materials for magnetic refrigeration require not only large magnitude but also reversibility, as well as room-temperature operating temperature, of the magnetocaloric effect. However, it is a complex problem to simultaneously meet these demands in the Heusler-type Ni-(Co)-Mn-X (X = In, Sn, Sb, Ga) magnetic shape memory alloys which are a promising candidate for magnetocaloric materials, owing to the interdependence of magnetostructural transformation parameters. Here, through synergic tuning of magnetostructural transformation parameters via alloying with Ti in Ni42- x Ti x Co9 Mn39 Sn10 alloys, we achieved a large reversible room-temperature magnetocaloric effect. By alloying with a proper amount of Ti, the martensitic transformation temperature was brought down to room temperature and the sensitivity of transformation temperature to magnetic field change was greatly enhanced with the transformation entropy change still remaining a large value, while the thermal hysteresis and the transformation interval only slightly increased. Thus, the field required to induce the complete and reversible transformation was significantly reduced. As a result, a large reversible room-temperature magnetic entropy change Δ S m of 18.7 J kg −1 K −1 under 5 T was achieved in the Ni41 Ti1 Co9 Mn39 Sn10 alloy. This is the first report on reversible Δ S m in Ni-Mn-Sn-based Heusler alloys and the Δ S m we achieved represents the highest reversible Δ S m under 5 T reported heretofore in Ni-Mn-based Heusler alloys. Furthermore, the Ni41 Ti1 Co9 Mn39 Sn10 alloy shows good compressive properties and stable martensitic transformation during thermal cycling, beneficial for potential magnetocaloric applications. This study is instructive for the development of high-performance magnetocaloric materials for room-temperature magnetic refrigeration. Graphical abstract: